(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: COVID-19 is defiantly most notifiable killing infectious disease in twenty-first century that to bring unprecedented deadly toll in human life. Many developing and under developing countries faces great challenges to provide treatment facilities to their country people. Pregnant women are not beyond that exception. Besides, they experience absence of sensible humanity that never happened in the history of recent past. Many of them risking their lives and they suffered premature delivery, IUD, Still birth, PPH and even death for unnecessary delay to reach and receive treatment due to social stigma about COVID-19. Methods: This study was conducted in Department of Obstetrics & Gynecology of COVID Dedicated Unit of Dhaka Medical College Hospital. 300 COVID-19 suspected obstetrical patients included conveniently. The study period was from July 2020 to August 2020. It was a prospective observational cross-sectional study. The study subjects were selected following convenience sampling technique. Results: In this study majority of the patient (62.2%) were in the age group 20-29, where age limit was 14 to 45 years. Majority of the patients (55.7%) was either Illiterate or could sign only. Around half (51.0%) of the patients had monthly family income <10,000 BDT. Of all cases, 57.7% were multipara, 37.7% were primipara and 4.6% were grand multipara. Among all, 43.38% had VD and 56.62% had LUCS. Out of them 3.68% were COVID-19 positive cases. Of all, 51% lived in the urban, 29% in sub-urban, and 20% in the rural area. In this study, 1.80% deaths within suspected cases, 14.28% death among admitted positive cases and there was no death found among suspected turned to positive cases. Among all, 9.55% babies were IUD & Still born, 2.20% needed ICU, where 0.73% mothers were positive, and 88.23% babies were normal where 2.94% mothers were positive mother. In present study, 4.33% needed HFNC/Ventilator support who were critically ill, out of them COVID-19 positive cases were 1.33%. Off all 300 patients, case fatality rate (CFR) was 0.67% where among all positive cases it was 4.56%. Conclusion: Pregnant woman being considered potentially vulnerable to viral infection. Physiological changes during pregnancy have a significant impact on different functional systems of body. COVID-19 also increases the risk and suffering many fold to pregnant women on different dimension of life. The ultimate outcome, most of the positive cases unencumbered themselves by the cost of their senseless suffering and life. JOPSOM 2020; 39(2): 45-49